Analisis Kritis Wacana Poligami: Praktik Marjinalisasi dan Demonologi Islam dalam Wacana Poligami - Khotimah, Ema (Mediator, 2008)
Polygamy (and also anti-polygamy) always become hot issue in Indonesia. There are at least two national events which reintroduced polygamy discourse: the second-marriage of famous religious leader—KH Abdullah Gymnastiar, and pornographic video depicting sexual relationship between Yahya Zaini—a high political figure—and Maria Eva—a wannabe celebrity. A strong and emotional debate over those two events marginalized the main issue of polygamy itself in the world of Islam. A critical discourse analysis toward polygamy discourse has found that marginalization practices are conducted even by prominent members of Islamic organizations and intellectuals, as well as members of legislative body. It turned out that polygamy discourse was biased and misrepresented.